Kaposi Sarcoma, a Trifecta of Pathogenic Mechanisms - Gabriela Rusu-Zota; Oana Mădălina Manole; Cristina Galeș; Elena Porumb-Andrese; Otilia Obadă; Cezar Valentin Mocanu (Diagnostics, 2022)
Kaposi’s sarcoma is a rare disease with four known variants: classic, epidemic, endemic and iatrogenic (transplant-related), all caused by an oncogenic virus named Human Herpes Virus 8. The viral infection in itself, along with the oncogenic properties of HHV8 and with immune system dysfunction, forms the grounds on which Kaposi’s Sarcoma may develop. Infection with HHV8 occurs through saliva via close contacts, blood, blood products, solid organ donation and, rarely, vertical transmission. Chronic inflammation and oncogenesis are promoted by a mix of viral genes that directly promote cell survival and transformation or interfere with the regular cell cycle and cell signaling (of particular note: LANA-1, v-IL6, vBCL-2, vIAP, vIRF3, vGPCR, gB, K1, K8.1, K15). The most common development sites for Kaposi’s sarcoma are the skin, mucocutaneous zones, lymph nodes and visceral organs, but it can also rarely appear in the musculoskeletal system, urinary system, endocrine organs, heart or eye. Histopathologically, spindle cell proliferation with slit-like vascular spaces, plasma cell and lymphocyte infiltrate are characteristic. The clinical presentation is heterogenic depending on the variant; some patients have indolent disease and others have aggressive disease. The treatment options include highly active antiretroviral therapy, surgery, radiation therapy, chemotherapy, and immunotherapy. A literature search was carried out using the MEDLINE/PubMed, SCOPUS and Google Scholar databases with a combination of keywords with the aim to provide critical, concise, and comprehensive insights into advances in the pathogenic mechanism of Kaposi’s sarcoma.